CROSS-CULTURAL ROMANCE: DIGITAL FICTION FORMULA IN LIBYA’S LA’NAT AL-‘ISHQ AND INDONESIA’S ABIGHEA - Nugraha, Reza Sukma; Farhah, Eva; Nurzanah, Azka (Adabiyyāt: Jurnal Bahasa dan Sastra, 2023)
The popularity of the digital literary platform Wattpad has been recognized globally, including in Indonesia and Libya. Among various studies on fiction published through Wattpad, this research focuses on a comparative analysis of romance formulas written by popular Wattpad authors from two countries: La'nat al-'Ishq by Hams Yosef in Libya and Abighea by Chelsea Karina Aelia in Indonesia. The main issue addressed in this study is whether romance stories in digital fiction from these countries share the same narrative formula despite the cultural differences between the authors and their readers. The comparison is conducted using John G. Cawelti’s theory of formulaic literature and a descriptive-analytical method. The findings indicate that the dominant formulas in both fictions are the idealization of the main characters, love triangles, and happy endings. This suggests that, although these works are set in different cultural and linguistic contexts, their romance formulas reflect universal desires and expectations of young readers concerning the romance genre.